What That Pig Said to Jesus : On the Uneasy Permanence of Immigrant Life - Garrison, Philip (Book collections on Project MUSE., 2017)
"Philip Garrison writes about two waves of the immigrant poor that have settled on the Columbia Plateau and throughout the American West. One, beginning in the 1930s and caricatured as Okies, encompassed hundreds of thousands of families from Arkansas, Kansas, Missouri, Oklahoma, and Texas and continued until about 1970. The second wave, since 1990, has come primarily from the Mexican Central Plateau, in even greater numbers. This book looks at immigration as "an identity makeover, one taking the form first of breakdown, then of reassembly, and finally of renewal""--Provided by publisher